"I'm thinking of a number. If you multiply
2 answers:
43+13=56 56/8=7 The number is 7. You basically just do the inverse/opposite of what it’s telling you to do to solve it. So instead of subtract, you add and instead of multiplying, you divide. You also do the steps in backwards order so you add them and then divide. Hope this helps!
First, set up an equation that models this statement. N is your variable because it’s the unknown Number. 8n-13=43 Then, add 13 on both sides so you have the variable and it’s coefficient alone. 8n-13=43 +13.+13 ________ 8n=56 Then, divide the variable and the coefficient by the coefficient. 8n=56 —. — 8. 8 Now you have your variable all by itself, and you have the persons number. n=7 Your number is 7.
You might be interested in
This is a model of 63÷6. :)
(-2,6) is the pair for this equation
Answer:55
Step-by-step explanation:
sike i lied that is so easy just try
Answer:
Step-by-step explanation:
Charlie has $27
He spent $3 for kid's meal for his little brother
Remaining money=27-3=$24
Number of Sandwiches he wants to buy = 6
Money he needs to pay for each sandwich = 24/6 = $4